Insights on Engineered Microbes in Sustainable Agriculture: Biotechnological Developments and Future Prospects - Sudheer, Surya; Bai, Renu G.; Usmani, Zeba; Sharma, Minaxi (Current Genomics, 2020)
Background: Enhanced agricultural production is essential for increasing demand of the growing world population. At the same time, to combat the adverse effects caused by conventional agriculture practices to the environment along with the impact on human health and food security, a sustainable and healthy agricultural production needs to be practiced using beneficial microorganisms for enhanced yield. It is quite challenging because these microorganisms have rich biosynthetic repositories to produce biomolecules of interest; however, the intensive research in allied sectors and emerging genetic tools for improved microbial consortia are accepting new approaches that are helpful to farmers and agriculturists to meet the ever-increasing demand of sustainable food production. An important advancement is improved strain development via genetically engineered microbial systems (GEMS) as well as genetically modified microorganisms (GMOs) possessing known and upgraded functional characteristics to promote sustainable agriculture and food security. With the development of novel technologies such as DNA automated synthesis, sequencing and influential computational tools, molecular biology has entered the systems biology and synthetic biology era. More recently, CRISPR/Cas has been engineered to be an important tool in genetic engineering for various applications in the agri sector. The research in sustainable agriculture is progressing tremendously through GMOs/GEMS for their potential use in biofertilizers and as biopesticides. Conclusion: In this review, we discuss the beneficial effects of engineered microorganisms through integrated sustainable agriculture production practices to improve the soil microbial health in order to increase crop productivity.
Keywords: inoculants